Manajemen Strategi Pendayagunaan Dana Zakat melalui Program Zmart di BAZNAS Kabupaten Sukabumi - Maulana Akbar, Saipul; Sabet Rahmawaty, Indira; Rustandi, Ridwan (Tadbir: Jurnal Manajemen Dakwah, 2026)
This study aims to analyze the management of the strategy for the utilization of zakat funds through the Zmart Program at BAZNAS Sukabumi Regency in improving the welfare of mustahik, using strategy management theory and descriptive qualitative methods. The objectives of this research: (1) How the formulation of the utilization of zakat funds is carried out to develop mustahik skills, both in terms of business skills and mustahik welfare; (2) How is the implementation carried out to ensure that mustahik is able to run and develop the business independently and sustainably; (3) How the evaluation is applied to measure the success of the program to enable, the use of productive zakat funds in achieving the goal of improving mustahik welfare.